Low Levels of Hepatocyte‐Specific Methylation in Cell‐Free DNA Are a Strong Negative Predictor for Acute T Cell–Mediated Rejection Requiring Treatment Following Liver Transplantation. Issue 6 (21st March 2022) - Cox, Daniel R. A.; Low, Nicholas; Goh, Su Kah; Lee, Eunice; Vago, Angela; Jackett, Louise; Lokan, Julie; Braat, Sabine; Jones, Robert; Testro, Adam; Dobrovic, Alexander; Muralidharan, Vijayaragavan
Abstract : Graft‐derived cell‐free DNA (gdcfDNA) quantification is a promising, minimally invasive tool for detecting acute T cell–mediated rejection (ATCMR) following liver transplantation (LT). We investigated the utility of measuring hepatocyte‐specific methylation in cfDNA (HS‐cfDNA) to quantify gdcfDNA, examining its accuracy in detecting ATCMR in a prospective, cross‐sectional study. Blood was collected from LT recipients immediately prior to graft biopsy for suspected rejection. HS‐cfDNA was quantified using droplet‐digital polymerase chain reaction. Prebiopsy liver function tests (LFTs) and HS‐cfDNA levels were correlated with biopsy results and the primary outcome of treated biopsy‐proven acute rejection (tBPAR). A total of 51 patients were recruited; 37 had evidence of rejection on biopsy and 20 required treatment. As much as 11 patients needed inpatient treatment for rejection. HS‐cfDNA significantly outperformed LFTs in identifying patients with tBPAR, particularly those needing inpatient treatment (area under the curve, 73.0%; 95% confidence interval, 55.4%‐90.6%; P = 0.01). At a threshold of <33.5% of the total cfDNA fraction, HS‐cfDNA had a specificity of 97%, correctly excluding tBPAR in 30/31 patients. Quantifying graft‐specific methylation in cfDNA has a major advantage over previous gdcfDNA techniques: it does not require genotyping/sequencing, lending it greater feasibility for translation into transplantation care. Low levels of HS‐cfDNA were a strong negative predictor for tBPAR (negative predictive value, 86%) and may have a future role in triaging patients prior to invasive graft biopsies. Abstract : https://www.wileyhealthlearning.com/#/online-courses/68c22ca7-1805-497a-98d1-9629059c9605